2016
DOI: 10.14269/2318-1265/jabb.v4n4p93-95
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and pH of the Meat of Broilers Submitted to Pre-Slaughter Heat Stress

Abstract: In order to evaluate the chemical composition and pH of chicken meat subjected to heat stress during the preslaughter rest time, an experiment was conducted in a slaughterhouse. Twenty-five birds were randomly selected and housed in rooms without air conditioning for a 3-hour period, with an average temperature of 33°C and relative humidity of 83%. After slaughter, the carcasses were deboned and prime cuts were chilled (between 0 and 4 °C) for 24 hours for analysis of moisture levels, protein, fat, ash, and pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our study, pH was not influenced by the inactive yeasts dietary supplementation. The raw broiler meat pH mean values ranged for raw breast (5.97-6.02) and thigh (5.91-6.02) and fitted in the 24 h raw refrigerated broiler's meat normal range of values [31,32] without abnormality encounters such as pale soft exudative and wooden-like meat characteristics. Generally, the meat pH is an important quality indicator, firmly associated with slaughtering, meat processing, and storage management.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, pH was not influenced by the inactive yeasts dietary supplementation. The raw broiler meat pH mean values ranged for raw breast (5.97-6.02) and thigh (5.91-6.02) and fitted in the 24 h raw refrigerated broiler's meat normal range of values [31,32] without abnormality encounters such as pale soft exudative and wooden-like meat characteristics. Generally, the meat pH is an important quality indicator, firmly associated with slaughtering, meat processing, and storage management.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sukoco et al (2015) reported that dietary inclusion of noni (Morinda citrifolia L.) leaves extract (at levels of 0.05, 0.10, 0.15, and 0.20%) did not affect physical quality, including pH, WHC, cooking loss andtenderness, of broiler breast meats. Several factors influence the physical characteristics of broiler meats; some of them are stress conditions before slaughter and pre-slaughter management (Sukoco et al, 2015;Fernandes et al, 2016). These latter factors may influence feed intake, digestion, and nutrient utilization, determining the glycogen stored in the muscle.…”
Section: Effect Of Plant-derived Products On Physical and Organolepti...mentioning
confidence: 99%
“…Prior to slaughter, 3 hours of stress leads to changes in the chemical composition and pH of poultry meat, manifestation of PSE signs [11]. At the same time, the main problem is associated with the decrease in the sensor characteristics of meat, which lead to an increase in technological losses when processing for meat products [12].…”
Section: Introductionmentioning
confidence: 99%